2018
DOI: 10.1016/j.ydbio.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

The switch from cAMP-independent to cAMP-dependent arrest of meiotic prophase is associated with coordinated GPR3 and CDK1 expression in mouse oocytes

Abstract: Mammalian oocytes are arrested in meiotic prophase from around the time of birth until just before ovulation. Following an extended period of growth, they are stimulated to mature to the metaphase II stage by a preovulatory luteinizing hormone (LH) surge that occurs with each reproductive cycle. Small, growing oocytes are not competent to mature into fertilizable eggs because they do not possess adequate amounts of cell cycle regulatory proteins, particularly cyclin-dependent kinase 1 (CDK1). As oocytes grow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…CDC25B is an essential regulator for meiotic resumption in mouse oocytes (27), and GPR3 potentiates meiotic competence by increasing cyclic AMP levels (28). The present results identified no significant differences in the expression levels of CDC25B and GRP3 between the tumor-bearing and control groups.…”
Section: Discussioncontrasting
confidence: 42%
“…CDC25B is an essential regulator for meiotic resumption in mouse oocytes (27), and GPR3 potentiates meiotic competence by increasing cyclic AMP levels (28). The present results identified no significant differences in the expression levels of CDC25B and GRP3 between the tumor-bearing and control groups.…”
Section: Discussioncontrasting
confidence: 42%
“…And these genes are essential factors for normal ovarian development [27,28]. Research has shown that small, growing oocytes in mouse are not competent to mature into fertilizable eggs because they do not possess adequate amounts of cell cycle regulatory proteins, particularly cyclin-dependent kinase 1 (CDK1) [29]. As oocytes grow, they synthesize CDK1 and acquire the ability to mature.…”
Section: Plos Onementioning
confidence: 99%
“…Previous studies have not revealed major defects in the timing of meiotic re-entry in oocytes from early antral follicles (Firmani et al, 2018), which is instead the hallmark of the Ccnb2 −/− phenotype. A word a caution is that the Ccnb2 gene is inactivated globally and possible defects in the somatic compartment cannot be formally excluded.…”
Section: Discussionmentioning
confidence: 87%